Development of Post-Occupancy Design Evaluation technique as a design studio criteria for future Open-plan System - Suaimi, Nursyuhada (2021)
Open-plan System (OPS) furniture nowadays becoming a trend for student's design studios in Malaysia university. Currently, there were no specific design criteria for OPS used by students. Besides, there was no standard evaluation technique to validate the relevancy of the product to the current user. There is a need to review the existing design criteria of OPS furniture used by students. To sustain the product quality in the future, the developed priority of design criteria will be used to create an evaluation form technique that is called Post-Occupancy Design Evaluation™ (PODE). This study seeks to identify the priority of design criteria of the OPS furniture for students used. This study also develops the PODE™ technique of OPS furniture standard guidance design criteria for students used. This study adopted a mixed- method approach. The first is qualitative method used in this study was through the researcher's experience as a student, review of literature, close-ended interview to gain the Designer Voice (DV), Participatory Design (PD) to gain the User Voice (UV), and pilot test on the Design Evaluation (DE) survey form development. While the quantitative method used in this study through the DE survey to identify the priority of design criteria of OPS furniture and the top rank of user’s requirement. The DE Form is a novel approach by the researcher that adopting the structure of House of Quality (HOQ) in Quality Function Deployment (QFD) approach. This study revealed that the priority of design criteria lead by the usability while sketching, ergonomic of the table, aesthetic in color, and function in flexibility. Other than that, the result also reveals that the user requirement change height and angle of a table for sketching has majority voted through the DE analysis. The PODE™ form has adopted the concept of the Post-Occupancy Evaluation (POE) which is focused on design evaluation as a template for a designer to evaluate the design in the future. It can be summarized that the priority of design criteria of OPS furniture used by the student are gained from the user’s opinion and thought which led to user satisfaction. PODE™ technique contributes to stakeholders for future furniture planning for student's studio which are the standard guidance for the designer to refer in future furniture design that will provide a quality product that meets the student's needs.